ANALISIS STRUKTUR, PERILAKU, DAN KINERJA INDUSTRI TEPUNG TERIGU DI INDONESIA - Cila Apriande; Arief Daryanto (Magister Science of Agribusiness, Department of Agribusiness, FEM-IPB University, 2012)
Flour is one of important crop commodity for Indonesian people. However, government interventions lead the formation of monopoli structure and capital accumulation. The purpose of the research is to analyze the structure, behavior and market performance of Indonesian flour industry. Structure-Conduct-Performance model is used to analyze the industry. The result shows that the industry structure is tight oligopoly where tight competition occurs among few big players. CR4 index is 76.3 percent and Hirchman-Herfindal Index is 3731.12. Price, as conduct indicator, is regulated by Flour Industry Association (Aptindo) with regards of international price and cost of transportation. Industry performance is inefficient or constable (either one or both) based on 10.75 PCM index. Government intervention is required to prevent market control by big players.